2021
DOI: 10.3390/biomedicines9111709
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Periodontal Bacteria with Chronic Inflammation Present in Patients with Metabolic Syndrome

Abstract: Metabolic syndrome (MS) is correlated with many chronic diseases, and so far is moderately followed and treated. The present study follows a correlation of the presence of pathogens (Fusobacterium nucleatum, Bacteroides forsythus, and others) in the gingival crevicular fluid and MS. (1) An important role in the fight against MS is to reduce fat mass, inflammatory mediators, and prevent cytokine-associated diseases. (2) A group of 111 people with MS was studied, divided into 3 groups. The control group (CG) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The presence of bacteria in the gingival crevicular fluid has been correlated with a pro-inflammatory process [54], but studies also emphasize a connection with colorectal cancer [22,[55][56][57], in neurodegenerative diseases [58], with cardiomyopathological risk [59], with arthritis [60], prostatic disease [61], or with proinflammatory process [27]. In the current study, the gingival crevicular fluid analyzes showed a high incidence of Fusobacterium nucleatum in patients with gastrointestinal problems (100.0%).…”
Section: Discussionsupporting
confidence: 47%
“…The presence of bacteria in the gingival crevicular fluid has been correlated with a pro-inflammatory process [54], but studies also emphasize a connection with colorectal cancer [22,[55][56][57], in neurodegenerative diseases [58], with cardiomyopathological risk [59], with arthritis [60], prostatic disease [61], or with proinflammatory process [27]. In the current study, the gingival crevicular fluid analyzes showed a high incidence of Fusobacterium nucleatum in patients with gastrointestinal problems (100.0%).…”
Section: Discussionsupporting
confidence: 47%
“…The links of IBS to neuro-mental problems, such as depression and anxiety, have been discussed in specialized studies [45,46]; nevertheless, these have been discussed for the rebalance of deficient microbiota [47]. Dysbiosis has also been associated with other chronic diseases (e.g., type 2 diabetes) [18,48] and periodontal disease [49]; these diseases are related to metabolic syndrome [50][51][52]. From this point of view, we followed five psychological parameters in order to correlate with the evolution of IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored the relationship between weight status and metabolic diseases and their therapeutical approaches [ 29 , 30 ]. Several studies have highlighted the direct link between obesity and metabolic syndrome [ 19 , 31 , 32 ], type 2 diabetes (T2DM) [ 8 , 33 ], with dysbiosis [ 34 , 35 ], and stress [ 36 , 37 ]. In our current study, we observed a higher prevalence of overweight and obesity among the patients.…”
Section: Discussionmentioning
confidence: 99%